Application of Functional Resonance Analysis Method to Sustain Human-Centered Design Practice in Road Construction. (September 2016) - Pazell, Sara; Burgess-Limerick, Robin; Horberry, Tim
The Functional Resonance Analysis Method (FRAM) involves mapping out interrelated functions to gain an understanding of how to monitor and optimize system performance. A FRAM model was applied to study the application of predictive, human-centered design review of an asphalt job truck for road construction. The model provided for a constructive means to communicate, reflect upon, and strategize methods to support ongoing human-centered design practice in the business. Practical recommendations were made with regard to resource allocation and management activity. This paper will describe the development of the model, the application, and the findings.